Estructura horizontal de especies comerciales del bosque de colina baja de la concesión forestal 16-LOR-MAY/CON-MAD-2018-026, distrito de Mazán, Loreto. 2022 - Paredes Yaicate, Jean Paul (2022)
The horizontal structure of commercial species of the low-hill forest of forest concession 16-LOR-MAY/CON-MAD-2018-026, district of Mazan, Loreto, was determined in this study. Data from the forest census of commercial species of harvesting unit No. 197 were evaluated. A total of 1390 trees were recorded, grouped into 24 forest species and 11 botanical families. Fabacea is the family with the highest number of species (six species). The number of trees by diameter class is 1,69 trees/ha (1390 trees), where Vochysia vismiifolia (0,44 trees/ha, 361 trees), Virola surinamensis (0,23 trees/ha, 188 trees), Parkia nitida (0,12 trees/ha, 101 trees), Hymenolobium pulcherrimum (0,11 trees/ha, 87 trees), and Osteophloeum platyspermum (0,10 trees, 82 trees), contain the highest number of trees. Ecologically, Vochysia vismiifolia (Vochysiaceae) is the most important with an IVI of 56,36%, followed by Virola surinamensis (28,44%), Parkia nitida (20,24%), Cedrelinga cateniformis (19,23%), Hymenolobium pulcherrimum (17,90%) and Brosimum rubescens (16,99%). The results show a highly significant difference between the averages of the horizontal structure among species.